Phase pure epitaxial growth of BiFeO3 films: An effect of oxygen partial pressure. (September 2017) - Chandra Das, Sadhan; Majumdar, Abhijit; Katiyal, Sumant; Poojitha, Bommareddy; Saha, Surajit; Shripathi, T.
Abstract: We report the growth of bismuth ferrite, BiFeO3 (BFO), thin films by varying oxygen partial pressure (230, 100 and 10mTorr) in pulsed laser deposition system using 10% bismuth excess BFO target on SrTiO3 (001) [STO] substrates at 700 °C each for 15 min duration. X-ray diffraction shows the presence of an impurity phase along with BFO peaks for 230 mTorr film, whereas oriented BFO film is observed for 100 mTorr film with a small impurity phase. Importantly, epitaxial growth of BFO is observed without any impurity phase and with sufficiently increased strain for the 10 mTorr film, confirmed by the reciprocal space mapping of (002) and (103) reflections. UV-Raman measurements have been performed on as grown films and the 10 mTorr BFO film after annealing up to 500 °C to check its thermal stability. Atomic force microscopic (AFM) study reveals that the 10 mTorr BFO film shows a lower roughness as compared to 100 mTorr and 230 mTorr films. Fast Fourier Transform (FFT) analysis in AFM shows a fourfold symmetric structure suggesting the presence of both modes of pattern-orientation in 230 mTorr BFO film whereas an elongated bright spot along the y-direction in the FFT of 10 mTorr BFO film suggests the growth tendency to be along the y-direction. Highlights: Bismuth ferrite (BFO) films were grown on STO substrates under different oxygen partial pressure. XRD, RSM, UV and Visible Raman, AFM and XRR measurements were done for 230, 100 and 10 mTorr BFO films. 10 mTorr BFO film was found to be single phase, fully strained and epitaxial. FFT of AFM reveals that 10 mTorr film has less roughness. 230 mTorr film was further annealed in vacuum for checking the stability of the film.